Analisis Pengaruh Marketing Mix Terhadap keputusan Membeli Batik - Adiakso, Gilang; , Ahmad Mardalis, S.E., M.B.A (2015)
This research was conducted at The Kencana Ungu Batik Surakarta, as the purpose of this study was to determine the influence of product, price, promotion and place on purchasing decisions at Rumah Batik Kencana Ungu. The sampling technique using a convenience sampling, the sampling design means that it's gathering information from members of the population who gladky willing to give and who has made a purchase, especially those on Kencana Ungu Batik Products, wuth guidelines for sampling 5 - 10 times the amount of indicator / item questionnaire variable studied, in order to get a sample of 90 respondents. While test analysis using multiple linear regression analysis, T - test, F - test, coefficient of determination ( R²). From this results it can concluded that the variable product, price, promotion and location significantly influence the decision to buy batik at Kencana Ungu either partially or simultaneously. From the research conducted found that the factors of the production, especially Batik Kencana Ungu should always increase attention to factor in the product marketing strategies.